Assuming I am reading this question correctly
Chat with our AI personalities
3x2(x2 - 3)
Factorizing is putting expressions into brackets to simplify them. For example 6x3+4x2+2x can be factorized into 2x(3x2+2x+1). When the bracket is multiplied out, it'll give the original expression: (2x*3x2)+(2x*2x)+(2x+1)=6x3+4x2+2x To do this needs a lot of trial and error to get the right combination of numbers and letters in and out of the brackets.
3x2 + 48 + 192 = 3x2 + 240 = 3 (x2+ 80)
This is an expression and you do not solve an expression, but you can factor this one.X2 + 3X4X2(1 + 3X2)========
d/dx 3x2/2 + 7